Acceptance of Electronic Labeling for Medicinal Product Information Among Malaysian Hospital Patients: Cross-Sectional Study - Xin Yee Loh; Ai Ling Woo; Azwa Haris; Cheryl Shajini Pereira; Bee Kim Tan (JMIR Publications, 2024)
BackgroundWhile perceptions of electronic labeling (e-labeling) in developed countries have been generally positive, existing data primarily come from studies involving hospital pharmacists, community pharmacy customers who may not be frequent medication users, and individuals receiving COVID-19 vaccines. ObjectiveThis study aims to assess e-labeling acceptance, perceptions of its benefits, challenges with its implementation, and preferences among hospital ambulatory care patients in Malaysia. Additionally, the study investigates the factors influencing patients' acceptance of e-labeling. MethodsA cross-sectional study using a 28-item questionnaire was conducted at the outpatient pharmacy department of a quaternary hospital in Kuala Lumpur, Malaysia, from May to June 2023. The questionnaire was developed based on a review of published literature related to e-labeling and was guided by the Unified Theory of Acceptance and Use of Technology, second version (UTAUT2). Patients aged 18 years and above were recruited using a stratified sampling method to ensure representative age-related medication usage. A mobile tablet was provided to patients for self-completion of the e-survey in their preferred language (English, Malay, or Mandarin). Categorical data on e-labeling acceptance, perceptions, and preferences were analyzed using descriptive statistics. Qualitative content analysis was performed to characterize participants' responses to open-ended questions. Univariate and multivariate binomial logistic regression analyses were conducted to identify predictors of e-labeling acceptance. ResultsOut of 462 patients approached, 387 (83.8%) participated in the survey, with 283 (73.1%) accepting e-labeling. Most participants perceived the electronic version of the package insert as beneficial, particularly for understanding their medication better through the choice of language (352/387, 91.0%). However, around half of the participants (197/387, 50.9%) expressed concerns about the potential risks of obtaining illegal medication information via e-labeling. Most participants (302/387, 78.0%) preferred to access electronic leaflets through government websites. However, 221/387 (57.1%) still wanted the option to request printed leaflets. Significant predictors of e-labeling acceptance included perceived benefits such as better understanding of medication (adjusted odds ratio [AOR] 8.02, 95% CI 2.80-22.97, P<.001), environmental protection (AOR 7.24, 95% CI 3.00-17.51, P<.001), and flexibility in information retrieval (AOR 2.66, 95% CI 1.11-6.35, P=.03). Conversely, being of Chinese ethnicity compared with Malay (AOR 0.28, 95% CI 0.13-0.60, P=.005) and perceived lack of self-efficacy in browsing electronic leaflets (AOR 0.25, 95% CI 0.11-0.56, P<.001) were associated with lower acceptance. ConclusionsThe acceptance rate for e-labeling among hospital ambulatory care patients was moderately high and was significantly influenced by ethnicity as well as patients' perceived benefits and challenges related to its implementation. Future strategies to enhance e-labeling uptake should address patient concerns regarding the challenges of using the digital platform and emphasize the benefits of e-labeling.